Plasmonic Au3Cu Ordered Nanocrystals Induced Phase Transformation in 2D-MoS2 for Efficient Hydrogen Evolution - Qamar U.; Roy S.; Kumar S.; Mukherjee B.; Devi A.A.S.; Goswami A.; Maiti P.; Das S. (My University, 2025)
The synthesis of ordered gold-copper (Au3Cu) alloy nanocrystals (≈10 nm) is reported and used in the semiconductor (2H) to metallic (1T) phase transformation of an atomically thin large-area 2D-MoS2 grown via CVD technique. The ordered Au3Cu nanocrystals are dispersed over 2D-MoS2, and the phase transformation is confirmed via Raman spectroscopy followed by X-ray photoelectron spectroscopy (XPS), while the surface properties of the Au3Cu/2D-MoS2 is determined by the XPS valence band analysis and ultra-violet photoemission spectroscopy (UPS). By comparing overpotential and Tafel slopes for Hydrogen Evolution Reaction (HER), a decrease is observed in overpotential by 83.2 mV and Tafel slope by ≈58.25 mV per decade for Au3Cu/MoS2 on light irradiation. This electrocatalytic enhancement of Au3Cu/MoS2 refers to the transformation of semiconducting 2D-MoS2 to metallic phase under light illumination, thereby altering the surface electronic structures, improving carrier concentrations, lowering the valence band edge, and lowering the free energy of H* adsorption/desorption. Density functional theory (DFT) calculations, along with other surface characterizations, further illustrate that the ordered nanocrystal-induced phase transformation in 2D-MoS2 leads to a more durable metallic characteristic, thus, enhancing the surface electrical conductivity, reducing surface potential and Gibbs free energy, and improving the kinetics of photoelectrocatalytic performance of the hybrid structure. © 2024 Wiley-VCH GmbH.